Long-acting cabotegravir plus rilpivirine for treatment in adults with HIV-1 infection: 96-week results of the randomised, open-label, phase 3 FLAIR study. Issue 4 (April 2021) - Orkin, Chloe; Oka, Shinichi; Philibert, Patrick; Brinson, Cynthia; Bassa, Ayesha; Gusev, Denis; Degen, Olaf; García, Juan González; Morell, Enrique Bernal; Tan, Darrell H S; D'Amico, Ronald; Dorey, David; et al.
Summary: Background: There is a need for more convenient, less frequent treatment to help address challenges associated with daily oral HIV treatment in people living with HIV, including stigma, pill burden, drug–food interactions, and adherence. The phase 3 ATLAS and FLAIR studies showed non-inferiority of long-acting cabotegravir and rilpivirine dosed every 4 weeks compared with standard oral therapy for the maintenance of virological suppression in adults with HIV-1 over 48 weeks. We present the 96-week findings. Methods: FLAIR is a randomised, phase 3, open-label, multicentre study done in 11 countries investigating whether switching to long-acting cabotegravir and rilpivirine is non-inferior to daily dolutegravir, abacavir, and lamivudine in virologically suppressed adults living with HIV-1. Antiretroviral therapy (ART)-naive participants received induction therapy with daily oral dolutegravir (50 mg), abacavir (600 mg), and lamivudine (300 mg) for 20 weeks. After 16 weeks, participants with less than 50 HIV-1 RNA copies per mL were randomly assigned (1:1) to continue the standard of care regimen (standard care group) or switch to receive daily oral cabotegravir 30 mg and rilpivirine 25 mg for at least 4 weeks followed by long-acting cabotegravir 400 mg and rilpivirine 600 mg, administered as two 2 mL intramuscular injections, every 4 weeks for at least 96 weeks (long-acting group). Randomisation was stratified by baseline (preinduction) HIV-1 RNA (<100 000 or ≥100 000 copies per mL) and sex at birth and used GlaxoSmithKline-verified randomisation software (RandAll NG, version 1.3.3) for treatment assignment. The primary endpoint was the proportion of participants with plasma HIV-1 RNA of 50 copies per mL or more assessed as per the US Food and Drug Administration (FDA) Snapshot algorithm at week 48, which has been reported previously. Here, we report the proportion of participants with 50 or more HIV-1 RNA copies per mL using the FDA Snapshot algorithm at week 96 (intention-to-treat population; non-inferiority margin 6%). The trial is registered with ClinicalTrials.gov, NCT02938520 . Findings: Between Oct 27, 2016, and March 24, 2017, 809 participants were screened. 631 (78%) participants entered the induction phase and 566 (70%) were randomly assigned to either the standard care group (283 [50%] participants) or the long-acting group (283 [50%]). Median age was 34 years (IQR 29 to 43), 62 (11%) were 50 years or older, 127 (22%) were women (sex at birth), and 419 (74%) were white. At week 96, nine (3%) participants in each arm had 50 or more HIV-1 RNA copies per mL, with an adjusted difference of 0·0 (95% CI –2·9 to 2·9), consistent with non-inferiority established at week 48. Across both treatment groups, adverse events leading to withdrawal were infrequent (14 [5%] participants in the long-acting group and four [1%] in the standard care group). Injection site reactions were the most common adverse event, reported by 245 (88%) participants in the long-acting group; their frequency decreased over time. Median injection site reaction duration was 3 days (IQR 2 to 4), and 3082 (99%) of 3100 reactions were grade 1 or 2. No deaths occurred during the maintenance phase. Interpretation: The 96-week results reaffirm the 48-week results, showing long-acting cabotegravir and rilpivirine continued to be non-inferior compared with continuing a standard care regimen in adults with HIV-1 for the maintenance of viral suppression. These results support the durability of long-acting cabotegravir and rilpivirine, over an almost 2-year-long period, as a therapeutic option for virally suppressed adults with HIV-1. Funding: ViiV Healthcare and Janssen Research and Development.